أثر آليات إبرام الصفقات العمومية على تطوير المؤسسات العمومية دراسة حالة مديرية الموارد المائية - دويدي عبد الرحيم; شيخاوي عبد الجبار; بورنان إبراهيم (جامعة عمار ثليجي الاغواط, 2022)
Public procurement is one of the most important aspects of state public spending, so the Algerian legislator was interested in its legislation and regulations, as it allowed the contracting interests to choose between the methods of concluding them, either requesting offers of all kinds or consenting with both types, but some contracting interests prefer the easy and short way of concluding deals according to Article 12 of Presidential Decree 247-15 that includes organizing public procurement and public utility authorizations, And the conclusion of deals in this Way requires the availability of conditions and circumstances that must be respected, but most of the contracting interests do not attach importance to the conditions necessary for this and authorize a reasoned decision to initiate the beginning of services before the conclusion of the public deal, without realizing the consequences of concluding this type of deals, so choosing the contracting interest for a specific dealer and granting him the deal It cannot be without justification because it strikes the principles and objectives of public deals.